1996
DOI: 10.1183/09031936.96.09030556
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of nitric oxide in human nasal airway

Abstract: The nasal output of nitric oxide (NO) is known to be high, but there have been varying reports of the exact level. We attempted to establish a quantitative measurement of nasal NO, and looked for a possible relationship with nasal resistance, at rest and during exercise.Nasal airway ventilation was performed by using an air pump at a constant flow rate, whilst the soft palate was elevated voluntarily. In a preliminary study, the flow rate for sampling was changed and concentrations of NO were measured. After d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 18 publications
3
47
1
Order By: Relevance
“…NO seems to play a pivotal role in these physiological functions as amongst others it has been shown that NO is involved in the regulation of the vascular tone in the nasal mucosa [25,30]. By this means NO is thought to modulate nasal vascular conductance and nasal cavity volume, which are correlated to the nasal airway resistance [16,17]. It should be noted however, that recent investigations, using high flow rate insufflation, contradict the existence of such a relationship [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO seems to play a pivotal role in these physiological functions as amongst others it has been shown that NO is involved in the regulation of the vascular tone in the nasal mucosa [25,30]. By this means NO is thought to modulate nasal vascular conductance and nasal cavity volume, which are correlated to the nasal airway resistance [16,17]. It should be noted however, that recent investigations, using high flow rate insufflation, contradict the existence of such a relationship [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the exact localization of NOS in nasal mucosa has been identified [14,15]. Furthermore, NOS activity seems to be involved in nasal vascular conductance and in nasal cavity volume [16,17]. Also NO, upon reaction with the superoxide anion radical and forming peroxynitrite, has been shown to act as potent cytotoxic effector molecule [18].…”
mentioning
confidence: 99%
“…Exhaled and nasal NO are markedly flow-dependent, and a significant reduction in NO concentrations has been reported when sampling or exhalation flow rates increase [5,10,13,31,39,40]. The probable reason for the reduction in NO concentration with increased expiratory or sampling flow is that the same amount of NO will be dispersed in a different exhaled or sample volume.…”
Section: Exhalation Parametersmentioning
confidence: 99%
“…Nasal NO measurements are also flow-dependent [40], and the importance of the dilution of nasal NO with the air from the lower airways cannot be overestimated. Thus, mean(±SEM) nasal NO levels in healthy children when sampled from the nose during tidal breathing through the mouth were 239±20 ppb, and were only 21±9.1 ppb during tidal nasal breathing [14].…”
Section: Nasal No Measurementsmentioning
confidence: 99%
See 1 more Smart Citation